Traduzione, riscrittura e manipolazione ideologica: le ‘cover’ delle canzoni di Dylan negli anni ‘60 (Altre Modernità, 2012)
This study investigates the translation of the lyrics of Bob Dylan’s songs into Italian. In particular, it focuses on the translations produced in the 1960s, when the Italian public was just starting to get acquainted with the most innovative cultural and artistic phenomena then occurring abroad, and in particular in the US. While in those days only a limited intellectual elite was seriously interested in such phenomena and in their political and artistic relevance, the record industry – then thriving – merely exploited them for the superficial appeal they could have on the public at large, at a time when a rising wave of juvenilism and xenophily was sweeping the still largely parochial scene of contemporary Italian culture. Against this background, this study discusses the main strategies adopted in the translation of Dylan’s texts into Italian, focusing on two among his most popular songs, “Blowin’ in the Wind” and “Rainy Day Women 12 & 35”, and shows that the translation evidently gives more consideration to the recipients’ tastes and to the record industry’s marketing strategies than to the original message, which is altered and deprived of its potentially subversive ideological value, an alteration also made possible by the failure to abide by copyright laws (Dylan’s authorship is not even acknowledge on record labels). The analysis not only contributes to shedding light on the cultural value of Dylan’s early works in Italian contemporary culture, but also provides the opportunity to discuss the ideological potential of the translator’s work, which, requiring a whole sequence of decisions, inherently offers a high potential for (more or less inadvertent) manipulation and ideological defusing.